Relatório de estágio técnico profissional em medicina veterinária: clinica medica e cirúrgica de ruminantes - Fiuza, Gabriel Pedro Nava (2023)
The agricultural sector has stood out for its growth and use of technologies used to meet the demand for expanding the genetic and nutritional potential and requirements of animals. Properties become increasingly effective and demanding, seeking knowledge and technology, so it is essential that the veterinarian is always trained and updated. In this sense, the technical-professional internship is the last challenge for the veterinary student. This is where all the study knowledge acquired during the undergraduate course is applied. During this period, the activities were guided and supervised by veterinarian Claudio Gomes Antunes; The academic guidance was provided by professor Dr. Maria Isabel Botelho Vieira. Thus, it was carried out at the headquarters of Cooperativa Tritícola de Espumoso Ltda, in the municipality of Espumoso-RS, covering 480 hours. During this stage, the activities carried out were: health and reproductive management; feed formulation; clinical care; discussions of diagnostics and therapeutic approaches for ruminants; surgeries; care for monogastric animals, horses and pigs. This report describes the activities carried out with a brief comment. In conclusion, there is a case report about a cesarean section, performed on a beef cattle farm, in an extensive system. Therefore, the technical-professional internship was extremely important for the intern’s professional and personal development. During this period, there was contact with other professionals in the area and with producers, providing opportunities to experience different realities, creating more knowledge about beef and dairy farming in southern Brazil, as well as new opportunities arising.